2010
DOI: 10.1007/s10964-010-9574-x
|View full text |Cite
|
Sign up to set email alerts
|

Sleep in Mexican-American Adolescents: Social Ecological and Well-Being Correlates

Abstract: A burgeoning body of research documents links between sleep and adjustment in adolescence, but little is known about the role of the social ecology in promoting healthful sleeping habits. This study was aimed at identifying the socio-cultural correlates of adolescents’ sleep, including average nighttime sleep duration, average daytime napping, and night-to-night variability in sleep duration and assessing the links between these dimensions of sleep and adjustment in Mexican American youth. Participants were 46… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
65
5
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(78 citation statements)
references
References 30 publications
7
65
5
1
Order By: Relevance
“…25 However, higher socioeconomic status is not necessarily protective because studies have also shown that youth from households with higher socioeconomic status have shorter sleep durations. 16,26 For older adolescents, additional environmental factors, such as after-school employment, 16 striving for good grades, 5,6,12 socializing, 27,28 participation in sports and other extracurricular activities, and lack of parental monitoring or rules about bedtimes, can further interfere with sleep durations. 6,29,30 School start times are reviewed later in the present report.…”
Section: Epidemiologic Studies Of Sleeping Adolescentsmentioning
confidence: 99%
See 1 more Smart Citation
“…25 However, higher socioeconomic status is not necessarily protective because studies have also shown that youth from households with higher socioeconomic status have shorter sleep durations. 16,26 For older adolescents, additional environmental factors, such as after-school employment, 16 striving for good grades, 5,6,12 socializing, 27,28 participation in sports and other extracurricular activities, and lack of parental monitoring or rules about bedtimes, can further interfere with sleep durations. 6,29,30 School start times are reviewed later in the present report.…”
Section: Epidemiologic Studies Of Sleeping Adolescentsmentioning
confidence: 99%
“…In summary, short sleep durations, coupled with evidence of daytime sleepiness (eg, increased self-reported sleepiness ratings, 5,6,11,31 daytime napping, 5,14,26 weekend oversleeping, 6,10,14,32 need for assistance in waking 6 ), as well as increased use of fatigue countermeasures (eg, excessive caffeine consumption 4,5,15 ), all indicate that adolescents are sleeping fewer hours than they need. The clear and consistent message is that middle and high school students are not getting enough sleep and that this issue is a chronic problem worldwide.…”
Section: Epidemiologic Studies Of Sleeping Adolescentsmentioning
confidence: 99%
“…d Includes 47 cross-sectional studies (Arman et al 2011;Barnes and Meldrum 2015;Biggs et al 2011;Bos et al 2009;Chen et al 2006;de Souza and Hidalgo 2014;Dewald et al 2012;Dewald-Kaufmann et al 2013;Do et al 2013;Fitzgerald et al 2011;Gangwisch et al 2010;Gupta et al 2002;Ievers-Landis et al 2008;Kang et al 2014;Kubiszewski et al 2014;Lam and Yang 2008;Lee et al 2012;Lehto and Uusitalo-Malmivaara 2014;Lemola et al 2015;Lin and Yi 2015;Lin et al 2011;Liu 2004;Liu and Zhou 2002;Lowry et al 2012;Lumeng et al 2007;McClure et al 2014;McHale et al 2011;McKnight-Eily et al 2011;Meijer et al 2010;Nixon et al 2008;Paciencia et al 2013;Pallesen et al 2011;Perfect et al 2014;Perkinson-Gloor et al 2013;Park et al 2013;Sarchiapone et al 2014;Silva et al 2011;Sivertsen et al 2014b;Short et al 2013aShort et al , 2013bStea et al 2014;Suzuki et al 2011;van der Heijden et al 2013;…”
Section: Harms/injuriesunclassified
“…b All studies used a subjective assessment of sleep with no psychometric properties reported (the quality of evidence was downgraded from low to very low). c Includes 17 cross-sectional studies (Arbabi et al 2015;Boschloo et al 2013;Eide and Showalter 2012;Kang et al 2014;Lin and Yi 2015;McHale et al 2011;O'Dea and Mugridge 2012;Pallesen et al 2011;Perkinson-Gloor et al 2013;Quevedo-Blasco and Quevedo-Blasco 2011;Short et al 2013a;Stea et al 2014;Stroebele et al 2013;Titova et al 2015;Unalan et al 2013;van der Vinne et al 2015;Wolfson and Carskadon 1998).…”
Section: Harms/injuriesmentioning
confidence: 99%
“…Previous studies showed that school schedules, such as starting time and school period, were significantly associated with children's sleep behaviors (Liu et al, 2005;McHale et al, 2011;Tynjälä et al, 1993;Wolfson, Spaulding, Dandrow, & Baroni, 2007;Zhang et al, 2010). It has been confirmed that early starting time of school may influence children's sleep habits and contribute to sleep deprivation and subsequent daytime sleepiness (Marhefka, 2011;Onyper, Thacher, Gilbert, & Gradess, 2012;Wolfson et al, 2007).…”
mentioning
confidence: 90%